The effectiveness of Sandplay Therapy in children who are victims of maltreatment with internalizing and externalizing behavior problems - MATTA, Reinalda Melo da; RAMOS, Denise Gimenez (Estudos de Psicologia (Campinas), 2023)
In article “The effectiveness of Sandplay Therapy in children who are victims of maltreatment with internalizing and externalizing behavior problems” with DOI: 10.1590/1982-0275202138e200036 published in Estudos de Psicologia (Campinas), 2021, 38, e200036 in the tables pages 6 and 7.